Negative Childhood Experiences and Risk Aversion: Evidence from Children Exposed to Domestic Violence - Marco Castillo (Institute of Labor Economics (IZA), 2020)
Using a longitudinal study of 1,900 Peruvian children, I show that children who grow up in a household where mothers report experiencing domestic violence are more risk averse and have lower cognitive development. Risk attitudes are measured with an incentivized experiment. The effect of domestic violence on risk attitudes is not mediated by cognitive development and suggests that early negative experiences in life can directly influence the risk attitudes of children. This experience is associated with other behavioral changes as well, including lower physical activity and higher BMI.
Keywords: C93; J13; 330; domestic violence; cognitive development; risk preferences; children